ISCRAM 2024 Proceedings - Penkert, Berthold; Hellingrath, Bernd; Rode, Monika; Widera, Adam; Middelhoff, Michael; Boersma, Kees; Kalthöner, Matthias (Proceedings of the International ISCRAM Conference, 2024)
The 21st Information systems for Crisis Response and Management (ISCRAM) Conference was held in Münster, Germany, from May 25th to 29th 2024. The conference followed a pracademic approach and was jointly hosted by the European Research Center for Information Systems (ERCIS) Competence Center for Crisis Management at the University of Münster and the State Fire Service Institute North Rhine-Westphalia, Germany. Taking a process-centric view on crisis management, the conference theme was “Embracing the Crisis Management Lifecycle.” The ISCRAM 2024 Proceedings includes information on the ISCRAM 2024 conference, conference and program committees, reviewers, sponsors, papers, best paper awards, workshops, project symposium, demonstrations, and posters.